2017
DOI: 10.1038/s41598-017-06666-2
|View full text |Cite|
|
Sign up to set email alerts
|

Strategies to Mitigate Variability in Engineering Human Nasal Cartilage

Abstract: Skin cancer and its associated treitments can have devastating consequences for survivors; this is particularly true when cancer occurs on the nose. Recent work has applied cell-based tissue engineering (TE) strategies to develop nasal cartilage constructs for reconstruction of the nose. In this study, we have generated human nasal cartilage on a clinically approved collagen scaffold to investigate the donor-to-donor variability of TE cartilage and evaluated strategies to mitigate it. We also evaluated the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Most significantly, after 3 weeks of implantation in nude mice, coculture constructs treated with 200 ng/mL of PTHrP prior to implantation showed no calcification, as demonstrated by absence of Alizarin Red S staining. In contrast, control coculture constructs revealed considerable Alizarin Red S staining after the 3 weeks of implantation, which is consistent with previous reports (Andrews et al, 2017). Again, this suggests that pre-treatment of coculture constructs with PTHrP, prior to implantation, improves the phenotypic stability of the constructs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Most significantly, after 3 weeks of implantation in nude mice, coculture constructs treated with 200 ng/mL of PTHrP prior to implantation showed no calcification, as demonstrated by absence of Alizarin Red S staining. In contrast, control coculture constructs revealed considerable Alizarin Red S staining after the 3 weeks of implantation, which is consistent with previous reports (Andrews et al, 2017). Again, this suggests that pre-treatment of coculture constructs with PTHrP, prior to implantation, improves the phenotypic stability of the constructs.…”
Section: Discussionsupporting
confidence: 91%
“…The pellets were retrieved; their gross appearance was recorded, stored in PBS, and fixed in 10% (v/v) formalin, as previously described. The pellets were processed, embedded, and sectioned for histology, as previously described (Andrews et al, 2017).…”
Section: Animal Implantationmentioning
confidence: 99%
See 2 more Smart Citations
“…PTHrP did not affect GAG matrix production. In addition, when chondro-induction was calculated, it was found that PTHrP did not affect the synergistic effect that has been both previously reported of NC:BM-MSC cocultures (Acharya et al, 2012;Andrews et al, 2017) and observed in this study. In addition, this was further supported by ACAN gene expression, which showed no significant change with PTHrP treatments.…”
Section: Discussionsupporting
confidence: 74%